High frequency of neurosyphilis in HIV‐positive patients diagnosed with early syphilis. Issue 5 (10th September 2015) - Firlag‐Burkacka, E; Swiecki, P; Cielniak, I; Siwak, E; Gizinska, J; Bakowska, E; Kubicka, J; Pulik, P; Kowalski, J; Podlasin, R; Horban, A
Abstract : Background: Syphilis is an infection frequently seen with HIV, and European guidelines on the management of syphilis suggest that HIV‐infected patients may have an increased risk of early neurological involvement, sometimes asymptomatic. Recent study shows a relationship between neurosyphilis and cerebrospinal fluid (CSF) HIV viral load (VL), which in turn may be associated with subsequent neurocognitive decline. Objectives and methods: The aim of the study was estimation of the frequency of neurosyphilis among HIV‐positive patients with early syphilis. The study included all patients diagnosed with early syphilis who had lumbar puncture performed in the years 2008–2012. Analysis included CSF parameters (serology, mononuclear cells, protein, glucose, chloride and lactate levels), CD4 count, serum VL and highly active antiretroviral therapy (HAART). Diagnosis of neurosyphilis was confirmed by CSF serology [positive fluorescent treponemal antibody and/or Venereal Disease Research Laboratory (VDRL) test(s)] and increased number of mononuclear cells. Statistical analysis included χ 2 tests with an accepted significance level of P < 0.05. Results: Lumbar puncture was performed in 72 patients, all men, with median age 33 (interquartile range 11) years. Neurosyphilis was confirmed in 65 (90.28%) of the patients. No statistically significant association between CSF parameters and CD4 count was found. However, statistically significant associations were found only between pleocytosis and serum VL > 1000 HIV‐1 RNA copies/mL ( P = 0.0451), as well as HAART treatment ( P = 0.0328). The proportion of confirmed neurosyphilis cases, also in patients with low serum VDRL titres, was very high. Conclusions: Considering the high proportion of patients who objected to having LP performed in the absence of neurological symptoms and the risk associated with this procedure, it may be preferable to use treatments with good CNS penetration in all HIV‐positive patients with early syphilis.